Correlation of leptin with clinico-pathological features of breast cancer - Abdulrazzaq, Saad Mohammed; Amjad, Nasser Muhammad; Al-Kubaisi, Muna Khaleel Dheyab; Harun, Norra (Innovare Academic Sciences, 2018)
Leptin is a multifunctional hormone produced mainly by adipocyte. Leptin and its receptor have long been found associated with breast cancer. Our aim is to investigate the correlation between Leptin/Leptin receptor and the clinico-pathological features of breast cancer. Blood samples for ELISA, tissue samples from tumours and adjacent breast tissue were taken from 51 women with breast cancer with a control group of 40 women with negative mammogram. Leptin and Leptin receptor in the tissues were estimated by immunohistochemistry (IHC). They were localized at subcellular level by immunocytochemistry using transmission electron microscopy TEM. Our results showed significant difference in serum leptin level between control and the patient group, but no difference between pre and post-operative levels in the patient group. By IHC, we found that majority of the breast cancer cells studied, stained positively for leptin and leptin receptors. Majority of the patients with distant metastasis were associated with high leptin and leptin receptor expression. TEM views both Leptin and Leptin receptor were found highly concentrated within and around the nucleus of the cancer cells, indicating nucleus is their principal seat of actions. However, presence of high concentration of leptin does not necessarily prove its over-expression, because it could be internalized from outside by leptin receptor in the cells. In contrast, leptin receptor is definitely over-expressed in the ductal breast cancer cells. We conclude that reducing leptin levels, blocking its downstream tissue specific signal transduction, and/or blocking the upstream leptin receptor pathway might help in prevention and therapy of breast cancer.